Kontribusi Lingkungan Belajar, Fasilitas Belajar, Dan Tingkat Sosial Ekonomi Orang Tua Terhadap Motivasi Berprestasi Dan Dampaknya Pada Hasil Belajar Matematika Siswa Kelas VIII SMP Negeri 2 Kartasura Tahun Ajaran 2016/2017 - Cahyanti, Yuli; , Prof.Dr. Sutama, M.Pd (2017)
Mathematics learning outcomes is important in the learning process to determine the level of students understanding of the material being studied in learning, The learning result is a result of the learning is non-physical activities such as changes in attitudes, knowledge, and prowess. The purpose of this research are to examine. 1) Contribution of the learning environment, learning resources, and socio-economic level of parents towards mathematics learning outcomes indirectly trough achievement motivation; 2) Contribution of the learning environment, learning resources, and the socio-leconomic level of parents towards the achievement motivation in mathematic; 3) Contribution of achievement motivation on learning outcomes in mathematic. This type of research is a kind of correlational study using a quantitative approach. The population in this study were 279 students. The sampling technique using proportional random sampling by lottery. Sample in this research are 165 students. Data collection techniques using the method of documentation and questionnaire method. Analysis using path analysis. Result of students data junior high school 2 Kartasura by categories of high, medium, low tend to have mathematics learning outcomes in the medium category with a percentage of 63.64% or 105 students out of 165 samples. The learning environment in the medium category with a percentage of 59.39% or 98 students out of 165 samples. The learning resources in the medium category with a percentage of 58.79% or 97 students out of 165 samples. socio-economic level of parents in the medium category with a percentage of 74.54% or 123 students out of 165 samples. The conclusions in the research. 1) There is a contribution the learning environment, learning resources, and socio-economic level of parents and significant impact on mathematics learning outcomes indirectly through motivation achievement, with a contribution of 65.1%; 2) There is a contribution the learning environment, learning resources, and socio-economic level of parents and significant achievement motivation, with a contribution of 47,7%; 3) There is a significant contribution to the achievement motivation and learning outcomes of mathematics, with a contribution of 52,85%.